MOBILE APP CONTROLLED AUTOMATION WITH ADMIN WEBSERVER LIVE MONITORING SYSTEM - SK, Jeevitha; Sivagami, Arasu (International Journal of Psychosocial Rehabilitation, 2020)
Smart IoT systems have been in interest to researches over years because of its capability, ease of use and flexibility to build systems like automation systems. Automation systems are those that work when certain set of tasks are assigned to work on its own and avoid any human intervention. In this project, architecture of a mobile app controlled automation system with admin web server live monitoring system is proposed. This system uses raspberry pi 3b+ as a server, Arduino mega 2560 as a microprocessor and a Bluetooth module which are controlled using a mobile app and a web application. This project can be capably organised to make it intense, harmless and machine-driven. Also, it can send alerts to the owner by using internet in case of any trespass and raises an alarm optionally. The strategic advantage obtained by choosing this system over the same kinds of existing systems is that the live status of the devices can be communicated to the user via the mobile application without having to refresh the system.